KEPEMIMPINAN BUPATI SIAK DALAM BIDANG PEMBANGUNAN PEREKONOMIAN PRIODE 2011-2016 - ", Gusmaksum; Amin, Raja Muhammad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Leadership or leader was important for sustainable success as a leader it is concerned with the direction, vision and focus on the development of a region, the success or failure of a person's economic development depends on leaders. This study was conducted to determine the leadership of Regent Siak in the field of economic development is applied, in this case the Regent Siak adopts a democratic leadership, Writer Want to examine more about Regent Siak Leadership in Economic Development Sector Period 2011-2016.The problem in this research is how the leadership of Regent Siak in the field of economic development and how the economic development of Siak and what are the factors that influence the economic development of Siak. The purpose of this study was to determine Siak district leader in the field of economic development, to determine the economic development of Siak and to determine the factors that influence the economic development of Siak. This study used a qualitative approach with descriptive qualitative research methods. The informants namely Regent Siak. Namely data collection techniques with interviews to determine the extent of the Regent Siak leadership in economic development. Qualitative data analysis technique that is performed on the data, in this case in the form of qualitative data informaasi then linked with other data to gain clarity and truth.Results of this study was the Regent of Siak in running the leadership has the properties that form in itself, namely intelligence, maturity and flexibility of social relationships, motivation and encouragement of achievement and attitudes of human relationships. In the development process prekonomian have seen that the economic development indicators such as per capita income, economic structure, savings rates, quality of life index, the human development index. Economic development can not be separated from the factors that affect the progress of, among others, resources, culture within the bureaucracy, political, social, science and technology.Keywords: Leadership, Economic Development